2014
DOI: 10.1603/me12261
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-Chromatographic Wicking Assay for the Rapid Detection of Dengue Viral Antigens in Mosquitoes (Diptera: Culicidae)

Abstract: There is a threat for dengue virus (DENV) reemergence in many regions of the world, particularly in areas where the DENV vectors, Aedes aegypti (L.) and Aedes albopictus (Skuse), are readily available. However, there are currently no accurate and reliable diagnostic methods to provide critical, real-time information for early detection of DENV within the vector populations to implement appropriate vector control and personal protective measures. In this article, we report the ability of an immuno-chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Many recent studies have detected the dengue virus in rural and urban settings of India and identified St. albopicta as a potential dengue vector [3,4]. A recent report on detecting dengue vector using Vector Test™ assay has suggested that the assay is highly specific and does not cross-react with other similar viruses [18]. The present study, probably due to the small sample size of St. albopicta mosquitoes used for detecting dengue virus was not able to identify dengue vectors but the present result cannot be generalised to the other areas where dengue outbreaks have been reported recently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent studies have detected the dengue virus in rural and urban settings of India and identified St. albopicta as a potential dengue vector [3,4]. A recent report on detecting dengue vector using Vector Test™ assay has suggested that the assay is highly specific and does not cross-react with other similar viruses [18]. The present study, probably due to the small sample size of St. albopicta mosquitoes used for detecting dengue virus was not able to identify dengue vectors but the present result cannot be generalised to the other areas where dengue outbreaks have been reported recently.…”
Section: Discussionmentioning
confidence: 99%
“…The VectorTest™ assay is a highly specific and rapid immunochromatographic assay for qualitative detection of any of the four serotypes of dengue virus (DENV 1–4) in the infected mosquito [18]. The assays were performed following standard manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…These assays allow for qualitative detection of arboviruses, and have the advantage of being rapid, without the need for specialized equipment. Currently, there are tests commercially available for a variety of viruses including CHIKV [ 44 ], DENV [ 45 ] and WNV [ 43 ], among others. In Singapore [ 46 ] and Malaysia [ 47 ], a dengue NS1 rapid test has been used to detect infected mosquitoes as part of a routine surveillance programme.…”
Section: Methods For Arbovirus Surveillancementioning
confidence: 99%
“…E2-specific mAbs developed previously in Chapter 3 were screened for their sensitivity and specificity (Goh et al, 2013). Purified mAbs were either conjugated with colloidal gold, or immobilized as capture antibodies on the test strips (Fernandez et al, 1994;Wanja et al, 2014). Instead of utilizing mosquitoes grinds, CHIKVROSS (GenBank ID: AF490259.3) virus culture was used in this preliminary test.…”
Section: Dipstick Antigen Assaymentioning
confidence: 99%
“…The rapid detection of CHIKV in mosquitoes via the use of a dipstick assay can provide a rapid and convenient surveillance tool for the prompt assessment of disease threat and timely implementation of vector control measures. These strategies are particularly useful during military deployments in high-risk areas (Nasci et al, 2003;Sattabongkot et al, 2004;Coleman et al, 2009;Wanja et al, 2014). However, when clinical samples positive for CHIKV RNA by RT-PCR were tested in the antigen-capture assay, the efficiency of CHIKV antigen detection was relatively poor, with only one out of 29 early-phase human samples positive.…”
Section: E2-specific Mabsmentioning
confidence: 99%